The Iconic Shape of the Traditional Javanese Food Oblok-Oblok - ., Sunarya; ., Alfiah; Kurniati Werdiningsih, Yuli (KnE Social Sciences, 2022)
Javanese traditional food includes a range of snacks and vegetables. The snacks come in various shapes and flavors. This article specifically explores the traditional oblok-oblok food. The Oblok-oblok food preparation differs based on the ingredients used. This study was field research. The authors after examining data on the name of the dish and the different processes of making it found that there were several variations of the traditional oblok-oblok foods. Using a qualitative method, this article attempts to explain the iconic aspects of the traditional vegetable using agih and padan analysis techniques. The agih technique directly analyzes the language elements without linking elements outside the language, for example, aspects of phonemes and morphemes contained in the name of the traditional food. The padan technique analyzes aspects of language by linking elements outside the language. The results showed that the traditional vegetable names had aspects of simplicity and suitability of the form of the food which is identical to the sound imitation (onomatopoeia) aspect of the blok, which describes the shape of the vegetable food as watery and concentrated. Keywords: iconic, traditional food, Oblok-Oblok